2001
DOI: 10.2214/ajr.176.1.1760167
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Radiography Findings in Small-Bowel Obstruction

Abstract: When both critical findings are present, the degree of small-bowel obstruction is likely high-grade or complete. When both signs are absent, small-bowel obstruction is likely low-grade or nonexistent. Upright abdominal radiographs are important in the examination of patients with suspected small-bowel obstruction and may contribute to the imaging triage of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(26 citation statements)
references
References 17 publications
1
21
1
3
Order By: Relevance
“…In our study, SBO was compared to the previously identified CT scout scans [25] [26]. These results corroborate recent reports [12].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, SBO was compared to the previously identified CT scout scans [25] [26]. These results corroborate recent reports [12].…”
Section: Discussionsupporting
confidence: 91%
“…Abdominal radiography carries a reported sensitivity and specificity ranging from 55% to 85% for the diagnosis of SBO; our CT scout scan sensitivity of 85% and specificity of 93% are substantially higher (2,8,9,12). This may be due to our selected patient population, because the patients referred for CT are more likely to have an SBO than the general population of patients referred for abdominal radiography.…”
Section: Discussionmentioning
confidence: 77%
“…While abdominal radiography is often still the preferred initial radiologic examination of symptomatic patients with SBO (7,8), computed tomography (CT) has gained favor because it can more consistently help determine the presence or absence of obstruction, as well as the cause, severity, and transition point of obstruction. In addition, CT can reliably depict secondary signs of bowel obstruction, such as abnormal wall thickening or enhancement, ascites, and pneumatosis.…”
mentioning
confidence: 99%
“…Although plain X-ray abdominal evaluation still remains the investigation of first choice in cases of suspected SBO due to its low cost and wide availability, it cannot reliably diagnose the exact level of obstruction and thus can only serve as a basis for triage for further imaging workup [5, 6]. …”
Section: Introductionmentioning
confidence: 99%